2015
DOI: 10.1039/c5sc03011k
|View full text |Cite
|
Sign up to set email alerts
|

Connecting electrodes with light: one wire, many electrodes

Abstract: The requirement of a wire to each electrode is central to the design of any electronic device but can also be a major restriction. Herein it is shown how electrodes can be connected using light such that a multielectrode device requires only a single physical wire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
144
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 84 publications
(148 citation statements)
references
References 23 publications
3
144
1
Order By: Relevance
“…Due to the pH-sensitive poly(methacrylic acid) shell, locally induced pH changes led to an increase of the thickness and a softer LbL structure. Another principle for locally induced photoelectrochemistry by light was established by Choudhury et al who termed the technique "light-activated electrochemistry" [92]. It is based on functionalization of redox-active species on oxide-free silicon surfaces to perform light-addressed Faradaic electrochemistry on the electrode surface [93,94].…”
Section: Addressable Photoelectrochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the pH-sensitive poly(methacrylic acid) shell, locally induced pH changes led to an increase of the thickness and a softer LbL structure. Another principle for locally induced photoelectrochemistry by light was established by Choudhury et al who termed the technique "light-activated electrochemistry" [92]. It is based on functionalization of redox-active species on oxide-free silicon surfaces to perform light-addressed Faradaic electrochemistry on the electrode surface [93,94].…”
Section: Addressable Photoelectrochemistrymentioning
confidence: 99%
“…Polymer Polystyrene TiO 2 [110] Polyaniline WO 3 [111] Polyaniline TiO 2 [111] Polypyrrol TiO 2 [56,111,112,114,115,122] Polypyrrol n-Si [55,92] Polypyrrol ZnO [113] Others Calcium alginate gels a:Si [110] Calcium alginate gels TiOPc [85,86] Chitosan a:Si [87,88] Polyhistidine-tagged proteins TiO 2 [89] DNA oligonucleotids n-Si [119] DNA oligonucleotids a:Si [120]…”
Section: Type Of Materials Deposited Materials Type Of Semiconductor Rementioning
confidence: 99%
“…The oxide levels are typically determined using x‐ray photoelectron spectroscopy (XPS). These results have motivated us to develop electrochemical devices on Si(100) electrodes protected from oxidation by using 1,8‐nonadiyne derived SAMs ,. Recently, we have begun to explore the electron transfer kinetics at these surfaces with ferrocene modified SAMs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we have shown that on molecularly smooth single crystal golds urfaces ( Figure 1) you can measure the impact of the potential of the electrical double layer above am onolayer modified electrode by changingt he positioning a redox speciesa bove am onolayer at 0.11nmi ncrements. [3] At times our electrochemical research has moved away from gold and alkanethiols, particularly when exploiting properties only availablew ith semiconductors [4] but somehow we always seem to drawn back to gold. [3] At times our electrochemical research has moved away from gold and alkanethiols, particularly when exploiting properties only availablew ith semiconductors [4] but somehow we always seem to drawn back to gold.…”
mentioning
confidence: 99%